Prescribing of strong opioid analgesics by UK primary care physicians from 2000 to 2010 - Zin, Che Suraya; Chen, Li-Chia; Knaggs, Roger D. (2012)
Background: Little is known about primary care physicians prescribing of opioids in the United Kingdom (UK). In the United State, it has been reported that increasing trends in opioid prescribing was also associated with increasing incidence of dependence and misuse, higher healthcare resources and higher death rate. Objective: This on-going study evaluated the prescribing trends of strong opioid analgesics for the treatment of pain in the UK primary care setting. Methods: This was a cross-sectional study using General Practice Research Database (GPRD) which is a large computerized database from 639 primary care practices throughout the UK from January 2000 to December 2010. Data were obtained from all patients prescribed a strong opioid-containing drug (buprenorphine, fentanyl, morphine and oxycodone) for pain management by using specific product codes. Total number of prescriptions for each drug was calculated. Descriptive statistics and simple linear regression were used to analyse proportion and yearly change in the number of prescriptions Results: A total of 2.77 million prescriptions were identified for all studied durgs over the 11 years period. The prevalence of morphine prescriptions was increased from 16 per 1000 prescriptions in 2000 to 78 per 1000 prescriptions in 2010, a statistically significant trend (p = 0.000). There were also statistically significant increased for fentanyl (2.5 to 31 per 1000 prescriptions), buprenorphine (2.4 to 43 per 1000 prescriptions) and oxycodone (0.3 to 36 per 1000 prescriptions) during the study period. Among the most common opioid containing-products prescribed for each type of drug were Oramoph® (morphine) oral solution 10mg/5ml (22%), Butrans® (buprenorphine) patches 5mcg (14%), fentanyl patches 25 mcg (26%) and Oxycontin® (oxycodone) modified release tablets 10 mg (12%). Conclusion: This preliminary study showed that the prescribing trend for strong opioid analgesics in the UK has increased significantly in the past eleven years. Further studies are required to better understand the reasons for and consequences of this trend.